Epitope mapping of recombinant Leishmania donovani virulence factor A2 (recLdVFA2) and canine leishmaniasis diagnosis using a derived synthetic bi-epitope. - Thais Melo Mendes; Eric Henrique Roma; Fernanda Costal-Oliveira; Lucas de Carvalho Dhom-Lemos; Cristina Monerat Toledo-Machado; Oscar Bruna-Romero; Daniella Castanheiras Bartholomeu; Ricardo Toshio Fujiwara; Carlos Chávez-Olórtegui (Public Library of Science (PLoS), 2017)
Leishmaniasis is one of the most important zoonotic diseases spread in Latin America. Since many species are involved in dog infection with different clinical manifestations, the development of specific diagnostic tests is mandatory for more accurate disease control and vaccine strategies.Seventy-five 15-mer peptides covering the sequence of recombinant Leishmania donovani virulence factor A2 (recLdVFA2) protein were prepared by Spot synthesis. Membrane-bound peptides immunoreactivity with sera from dogs immunized with recLdVFA2 and with a specific anti-recLdVFA2 monoclonal antibody allowed mapping of continuous B-cell epitopes. Five epitopes corresponding to the N-terminal region of recLdVFA2 (MKIRSVRPLVVLLVC, RSVRPLVVLLVCVAA, RPLVVLLVCVAAVLA, VVLLVCVAAVLALSA and LVCVAAVLALSASAE, region 1-28) and one located within the repetitive units (PLSVGPQAVGLSVG, regions 67-81 and 122-135) were identified. A 34-mer recLdVFA2-derived bi-epitope containing the sequence MKIRSVRPLVVLLVC linked to PLSVGPQAVGLSVG by a Gly-Gly spacer was chemically synthesized in its soluble form. The synthetic bi-epitope was used as antigen to coat ELISA plates and assayed with dog sera for in vitro diagnosis of canine visceral leishmaniasis (CVL). The assay proved to be highly sensitive (98%) and specific (99%).Our work suggests that synthetic peptide-based ELISA strategy may be useful for the development of a sensitive and highly specific serodiagnosis for CVL or other parasitic diseases.